Silvopastoral system restoration under changing climate and land use: improving sustainability and efficiency - Louhaichi, Mounir; Hassan, Sawsan; Gamoun, Mouldi; Slim, Slim; Jamel, Kailene (International Center for Agricultural Research in the Dry Areas, 2022)
Travelling workshop was conducted during 19–21 October 2022 with total number of 124 participants including farmers from Oued Sbaihia and Gueffaya, Tunisia, experts from ICARDA, the General Directorate of Forests, and the Higher School of Agriculture of Mateur. The main objective of the traveling workshop was to increase awareness of farmers about sustainable silvopastoral restoration under changing climate and land use. Specific objectives include 1) demonstrate best practices for introducing forage legume species (sulla), multi-purposes shrub/tree and grazing management and 2) distribute sulla seeds to interested farmers. This travelling workshop was organized to be interactive and to share knowledge, lessons learnt and good practice, and of the kinds of problems which farmers face. Based on the discussion among the involved stakeholders’ recommendations were made.